Google classroom: Perception and acceptance of online learning among Malaysian secondary school teachers - Lau, Jacqueline Chung Ling (2023)
Throughout the years, teaching methodologies have gradually transformed from traditional methods to technology-based teaching methods. Amongst many available online learning tools, Google Classroom as a Learning Management System has emerged as a popular option for educational purposes. Thus, this study aimed to determine the perception and acceptance of Google Classroom among Malaysian secondary school teachers. The first research objective is (1) to determine the influence of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, and behavioral intention on use behavior of GC among Malaysian secondary school teachers. The second and third research objectives are (2) to explore the benefits and challenges faced by Malaysian secondary school teachers while adopting Google Classroom, and (3) to explore the suggestions given by Malaysian secondary school teachers for the better adoption of Google Classroom. This study took a mixed-methods approach in conducting the study. A total of 406 secondary school teachers from West and East Malaysia participated in the survey, and 31 secondary school teachers participated in the interviews. Overall, four of the 10 proposed hypotheses were supported. Performance expectancy and hedonic motivation significantly influenced the behavioural intention, habit significantly influenced both behavioral intention and use behavior of Google Classroom among the teachers. The most perceived benefit of Google Classroom is the ease of marking homework and giving feedback. The most prevalent challenge encountered is the students’ discipline and attitude problems during online teaching and learning. As for the suggestion, most of them recommended to improve the Internet connection and gadgets. The findings show that Google Classroom is highly applicable in schools amidst the COVID-19 pandemic. The findings of this study will assist stakeholders in understanding the use of Google Classroom in schools and making appropriate judgments about its use among teachers.